Wastewater treatment and reclamation: a review of pulp and paper industry practices and opportunities - Hubbe, Martin A. (2017)
The pulp and paper (P&P) industry worldwide has achieved substantial progress in treating both process water and wastewater, thus limiting the discharge of pollutants to receiving waters. This review covers a variety of wastewater treatment methods, which provide P&P companies with cost-effective ways to limit the release of biological or chemical oxygen demand, toxicity, solids, color, and other indicators of pollutant load. Conventional wastewater treatment systems, often comprising primary clarification followed by activated sludge processes, have been widely implemented in the P&P industry. Higher levels of pollutant removal can be achieved by supplementary treatments, which can include anaerobic biological stages, advanced oxidation processes, bioreactors, and membrane filtration technologies. Improvements in the performance of wastewater treatment operations often can be achieved by effective measurement technologies and by strategic addition of agents including coagulants, flocculants, filter aids, and optimized fungal or bacterial cultures. In addition, P&P mills can implement upstream process changes, including dissolved-air-flotation (DAF) systems, filtration save-alls, and kidney-like operations to purify process waters, thus reducing the load of pollutants and the volume of effluent being discharged to end-of-pipe wastewater treatment plants.